An observation on the diving behavior of Cyrtodactylus consobrinus (Squamata: Gekkonidae) from Borneo - Chen, Hao Sen; Ace Kevin, S. Amarga; Lin, Yu Sing; Sen, Chin Chia; Indraneil, Das; Lin, Si Min (Escola Superior de Agricultura Luiz de Queiroz Departamento de Ciências Biológicas Laboratório de Zoologia de Vertebrados, 2024)
Cyrtodactylus consobrinus (Peters, 1871) is a forest-inhabiting gekkonid endemic to Southeast Asia. It has been known to occur in Peninsular Malaysia, extending to Sumatra, Pulau Sinkep and Borneo (Das 2010, Uetz et al. 2024), while a recent study restricted the species to western Borneo (Davis et al. 2023a, b), where it inhabits lowland forests and often observed foraging on tree trunks (Das 2010). This species was described under the name Gymnodactylus consobrinus by the German naturalist Wilhelm Karl Hartwich Peters (1815–1883), based on a single specimen collected from Sarawak, currently a Malaysian state on the island of Borneo (Peters 1871). Subsequently, it was listed under the genus Cyrtodactylus by Grandison (1972). Little is known about several aspects of the natural history of C. consobrinus, including its behavior. In this paper, we present an additional account on the anti-predator behavioral response of C. consobrinus.